The role of children`s literature in the patriotism, and the upbringing of Kurdish children = Rola literatury dziecięcej w patriotyzmie i wychowaniu dzieci kurdyjskich - Farhang Muzaffar Muhammad (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Children`s literature, despite being a relatively young branch of literature in general, is an important factor in the upbringing of children. Its basic aims have been obvious but not simple to achieve - to develop a child`s personality, provide educational experiences and encourage him to read. Along with areas such as art, theater, puppetry, music, movement and field trips, literature is also an object of children`s attention.
Keywords: children`s literature; Kurdish children`s literature; Kurdish culture; Kurdish nationalism; role of education; literatura dziecięca; kurdyjska literatura dziecięca; kultura kurdyjska; kurdyjski nacionalizm; rola edukacji